Evaluating ROI of the Cordova Edupartment Building Project for Long-Term Profitability - Rini Pebri Utari; Abdul Samad (Rekayasa Sipil, 2026)
Rapid population growth has increased housing demand, while limited land availability has encouraged the development of vertical residential buildings. The Cordova Edupark Apartment in Semarang is an education–religious–based apartment project planned to begin operations in 2025, with a design life of 50 years. Current project planning predominantly emphasizes initial construction costs and often neglects long-term costs incurred during the building's operational phase. This study evaluates the building’s life cycle cost (LCC). It assesses long-term investment feasibility by positioning Return on Investment (ROI) as the core investment evaluation framework, integrated with future-value-based financial analysis. The analysis refers to Ministry of Public Works Regulation No. 24/PRT/M/2008 and relevant local regulations on maintenance costs and tariffs. The research object is a 19-story apartment building with a total floor area of 39,423 m². The research stages include technical and financial data collection; LCC calculation covering construction, operation, maintenance, component replacement, demolition, and loan interest; and investment feasibility analysis under several occupancy and rental price scenarios. The results indicate that the total LCC over a 50-year service life amounts to Rp1,446,963,144,027, with maintenance costs constituting the largest proportion (±41%), followed by operational costs (±25%). Under the optimistic scenario, with a rental rate of Rp155,000/m² and an initial occupancy rate of 85%, the ROI-based feasibility analysis yields a positive Net Present Value (NPV) of Rp863,392,832,379, an Internal Rate of Return (IRR) of 19.31% exceeding the 6.78% Minimum Attractive Rate of Return (MARR), and a break-even period of 12.17 years.